Isotopic niche differentiation in benthic consumers from shallow-water hydrothermal vents and nearby non-vent rocky reefs in northeastern Taiwan. (July 2021) - Wu, Jing-Ying; Lin, Siou-Yan; Peng, Shao-Hung; Hung, Jia-Jang; Chen, Chen-Tung Arthur; Liu, Li-Lian
Highlights: The shallow-water hydrothermal vents off the Kueishan (KS) Islet, Taiwan, are known to emit the most acidic fluid (pH 1.52). The predominant vent crab Xenograpsus testudinatus mainly feeds on dead zooplanktons. In this sulfur-rich ecosystem and nearby non-vent rocky reefs (NV), the trophic niche width of benthic organisms with different feeding guilds was compared. We found that the contribution of plankton-derived production (i.e., dead zooplankton killed by sulfurous plumes) plays a significant role in providing food to benthic consumers, not only scavengers, such as vent crabs but also carnivores in SV off KS Islet. Abstract: Shallow-water hydrothermal vents (SVs) off Kueishan (KS) Islet are located along the northeastern coast of Taiwan. Although the trophic relationships of the sublittoral (15–30 m) and upper bathyal (200–300 m) vents in this region have been investigated, a comparison of SVs and adjacent non-vent ecosystems has not been undertaken. We compared the trophic structure and isotopic niche width of consumers in benthic communities around SVs off KS Islet with nearby non-vent rocky reefs (NV) to address this gap. The trophic structures for both SV and NV habitats were categorized into four trophic levels based on δ 13 C and δ 15 N signatures. SV sites ranged from −27.7 to −14.3‰ (δ 13 C) and from −7.3 to 12.2‰ (δ 15 N), whereas NV sites ranged from −20.2 to −13.1‰ (δ 13 C) and from 2.2 to 11.9‰ (δ 15 N). We found a notable difference in δ 13 C and δ 15 N values for primary producers and sediment organic matter between the two habitats indicating that available nutrient sources were different and more diversified in SV than those in NV. Based on the types of consumer feeding guilds, no difference in niche width of filter feeders between SV and NV was detected by ellipses analysis. Besides, a narrower niche width for scavengers in SV and differentiated niche positions for carnivores in both habitats were found. We conclude that plankton-derived production (i.e., dead zooplankton killed by sulfurous plumes) plays a significant role in providing food to benthic communities. These include not only scavengers, such as vent crabs, but also carnivores in SVs off KS Islet where extreme values of pH (1.52), temperature (116 °C), and H2 S (172 mmol/mol) are known to occur.